2019
DOI: 10.1038/s41593-019-0399-y
|View full text |Cite
|
Sign up to set email alerts
|

Proneural factors Ascl1 and Neurog2 contribute to neuronal subtype identities by establishing distinct chromatin landscapes

Abstract: Developmental programs that generate the astonishing neuronal diversity of the nervous system are not completely understood and thus present a significant challenge for clinical applications of guided cell differentiation strategies. Using direct neuronal programming of embryonic stem cells, we found that two main vertebrate proneural factors, Ascl1 and Neurog2, induce different neuronal fates by binding to largely different sets of genomic sites. Their divergent binding patterns are not determined by the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 71 publications
10
139
0
Order By: Relevance
“…To understand the molecular mechanisms of general neuronal fate committed to CR neurons identities, we focus on the genetic network of some key transcription factors that may predominate the differentiation progression. Ebf2 is enriched in Cluster 2 and its target genes has been identified in Neurog2-induced neurogenesis from mESC assays recently (38). We found that 457 of the early phase C157 genes and 611 of the intermediate C0346 genes were the target genes of EBF2 during neural differentiation, implying that it might affect the molecular pathways of CR neuron differentiation (Table S1).…”
Section: Transcriptional Factors Involved In Transitions In Gene Exprmentioning
confidence: 61%
“…To understand the molecular mechanisms of general neuronal fate committed to CR neurons identities, we focus on the genetic network of some key transcription factors that may predominate the differentiation progression. Ebf2 is enriched in Cluster 2 and its target genes has been identified in Neurog2-induced neurogenesis from mESC assays recently (38). We found that 457 of the early phase C157 genes and 611 of the intermediate C0346 genes were the target genes of EBF2 during neural differentiation, implying that it might affect the molecular pathways of CR neuron differentiation (Table S1).…”
Section: Transcriptional Factors Involved In Transitions In Gene Exprmentioning
confidence: 61%
“…Some data indicate that Ngn2, when using an appropriate conversion medium, not only binds most of the Ascl1 binding sites in fibroblasts, but also possesses many additional binding sites [30,33]. However, other data suggest that Ascl1 and Ngn2 possess divergent binding patterns that result in distinct chromatin states and different neuronal fates [34]. While further (meta-)analysis will likely shed more light on these different views, it is not surprising that the most efficient and reliable conversion strategies involve the combined expression of Ascl1 and Ngn2 [9,10,31,35].…”
Section: Enabling In Conversionmentioning
confidence: 99%
“…1A). The epigenetic identity of the starting cell population and remnant signaling cues present during the fibroblast-to-iN transition state finally determine subtype identity [23,34]. In highly heterogeneous cell populations, such as astrocytes in the rodent brain or primary human fibroblasts, the subtype of the starting cell type was shown to determine subtype outcomes of the iNs [73].…”
Section: Subtype-specific In Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of in vitro cell fate reprogramming has demonstrated that overexpression of specific TF combinations can be sufficient to drive specification of the same starting cells towards diverse cell types in the absence of other context-specific variables (Nakamori et al 2017;Pfisterer et al 2011;Zhao et al 2015;Masserdotti et al 2016). Therefore, cellular reprogramming provides a controlled system in which to investigate how TFs cooperate and modulate each other's functions for cell fate specificity in the absence of other differences in cellular context (Aydin et al 2019).…”
Section: Introductionmentioning
confidence: 99%